Perancangan dan Desain Alat Press Hidrolik Kapasitas Maksimal 10 Ton - Sarif, La; Sudarsono, Sudarsono; Sudia, Budiman (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2018)
Hydraulic press as a tool for molding material. This study aims to design and design tools with a maximum level of 10 tons and to determine the components and dimensions of the press. In this study the center uses the jack as the center of loading. For the size of this height 78 cm and width45 cm with bolt fasteners using clay steel material with 0.22 (%) C with tensile strength 42 (kg/mm2), shear stress 3 (kg / mm2), and the outer bolt diameter is 60 (mm) with a distance for the 5.5 (mm) M60 bolt crusher. As for the strength of the material from the components of the press tool has a permit voltage of 37 (kg / mm2), a bending moment of 750 x 103 (kg / mm) with a moment of inertia of 360 x 103 (mm4) and a voltage of 31.25 (kg / mm2). For governance factors 1.18 (kg/mm2).Keywords: Tool, hydraulic, design, safety factor